Digital Transformation and Technological Innovation on Higher Education Post-COVID-19 - Deroncele-Acosta, Angel (2023)
The university is an important pillar in sustainable development; however, COVID-19 imposed new dynamics that called for rethinking university praxis to achieve this mission, and although the systematization of good practices is a powerful mechanism for understanding educational success, this perspective of positive change has been little developed. Hence, the present study aimed to identify positive cores of faculty in their successful post-COVID-19 performance. A qualitative methodological approach was deployed, with the Netnography method, complemented with elements of positive psychology, appreciative inquiry, and management of formative potentialities. The online community consisted of 1238 university teachers from 10 Latin American countries, who participated for two months in an appreciative interview as an asynchronous journey of constructive proposals, for the active co-construction of post-COVID-19 success factors. The findings reveal multiple affirmative topics grouped into nine positive cores, identifying two target categories: digital transformation and technological innovation, as well as the processes directly associated with their dynamization. Finally, the epistemic implications of the findings in theory and practice, and their relevance in the creation of a formative agenda of positive change for Latin American Higher Education, are presented.